DYSTOCIA DUE TO FOETAL ANASARCOUS CO-TWIN IN A KANNI DOE AND ITS OBSTETRICAL MANAGEMENT - R. Suresh Kumar; T. Sarath; S. Rangasamy; U. S. Kalyaan; J. Umamageswari; C. Pugazharas; K. Krishnakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A full term pluriparous Kanni doe was presented with the history of difficulty in parturition, bloody vaginal discharge and straining. Based on the obstetrical examination, the case was diagnosed as dystocia due to foetal anasarca. The present communication places on record the successful per vaginal delivery of a foetal anasarcous co-twin.